Shusterman's somaesthetics : from hip hop philosophy to politics and performance art - Abrams, Jerold J. (Studies in somaesthetics : embodied perspectives in philosophy, the arts and the human sciences, ISSN 2451-8646, 2022)
"This edited collection provides an in-depth and wide-ranging exploration of pragmatist philosopher Richard Shusterman's distinctive project of "somaesthetics," devoted not only to better understanding bodily experience but also to greater mastery of somatic perception, performance, and presentation. Against contemporary trends that focus narrowly on conceptual and computational thinking, Shusterman returns philosophy to what is most fundamental-the sentient, expressive, human body with its creations of living beauty. Twelve scholars here provide penetrating critical analyses of Shusterman on ontology, perception, language, literature, culture, politics, aesthetics, cuisine, music, and the visual arts, including films of his work in performance art"--
Keywords: Shusterman, Richard; Aesthetics : Physiological aspects; Human body (Philosophy); Pragmatism; Arts : Philosophy; Philosophy, American : 21st century; filosofia; pragmatismi; estetiikka; somaestetiikka; esittävät taiteet; ruumiillisuus